2014
DOI: 10.4103/0970-9185.125701
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine prolongs the effect of bupivacaine in supraclavicular brachial plexus block

Abstract: Background:We compared the effects of adding dexmedetomidine to a 30 ml solution of 0.325% bupivacaine in supraclavicular brachial plexus block. Onset and duration of sensory and motor block along with the duration of analgesia were the primary endpoints.Materials and Methods:Fifty patients posted for upper limb surgeries were enrolled for a prospective, randomized, double-blind, placebo-controlled trial. Patients were divided into two groups, the control group S and the study group SD. In group S (n = 25), 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
119
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 28 publications
11
119
3
1
Order By: Relevance
“…Gandhi et al [20] reported that the onset time of sensory and motor block was shorter in the groups for which 38 ml of 0.25% bupivacaine and 30 µg of dexmedetomidine were added than the groups for which dexmedetomidine was not added; however, the duration of analgesia, motor and sensory block was about 4-6 times longer in the groups for which dexmedetomidine was given. Agarwal et al [15] reported that, with the use of 30 ml of 0.325% bupivacaine and 100 µg of dexmedetomidine, sensory and motor block onset time in the group for which dexmedetomidine was added was shorter, in contrast with the findings of Gandhi et al [20], but that the duration of analgesia, sensory and motor block was similarly longer.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Gandhi et al [20] reported that the onset time of sensory and motor block was shorter in the groups for which 38 ml of 0.25% bupivacaine and 30 µg of dexmedetomidine were added than the groups for which dexmedetomidine was not added; however, the duration of analgesia, motor and sensory block was about 4-6 times longer in the groups for which dexmedetomidine was given. Agarwal et al [15] reported that, with the use of 30 ml of 0.325% bupivacaine and 100 µg of dexmedetomidine, sensory and motor block onset time in the group for which dexmedetomidine was added was shorter, in contrast with the findings of Gandhi et al [20], but that the duration of analgesia, sensory and motor block was similarly longer.…”
Section: Discussioncontrasting
confidence: 55%
“…Many studies have reported that the addition of dexmedetomidine to a local anesthetic as an adjuvant in ultrasound-guided supraclavicular brachial plexus block application increases the duration of sensory and motor block [8,9,14,15,20]. Gandhi et al [20] reported that the onset time of sensory and motor block was shorter in the groups for which 38 ml of 0.25% bupivacaine and 30 µg of dexmedetomidine were added than the groups for which dexmedetomidine was not added; however, the duration of analgesia, motor and sensory block was about 4-6 times longer in the groups for which dexmedetomidine was given.…”
Section: Discussionmentioning
confidence: 99%
“…AgarwalSandhya et al (26) in their study showed that dexmedetomidine is a useful adjuvant to bupivacaine in brachial plexus block. Swami et al (27) compared clonidine and dexmedetomidine as an adjuvant to local anaesthetic agent in supraclavicular brachial plexus block with respect to onset and duration of sensory and motor block and duration of analgesia.…”
Section: Figurementioning
confidence: 99%
“…[22][23][24] The main advantage of simultaneous use of an adjuvant compound is to reduce the dose and frequency of administration of the main active drug, thus reducing side effects. 22,23,25 Clonidine, a centrally acting α 2 -adrenoceptor agonist, is administrated as an adjuvant of analgesic and hypnotic compounds. However, its main disadvantages are the incidence of hypotension.…”
Section: Introductionmentioning
confidence: 99%